EVALUASI ANGGARAN APBD SATUAN KERJA PERANGKAT DAERAH BADAN PERENCANAAN PEMBANGUNAN DAERAH (BAPPEDA) KABUPATEN KONAWE TAHUN ANGGARAN 2016 - Irdawati Irdawati (Jurnal Akrab Juara, 2018)
This study is intended to determine the results of the SKPD budget assessment at Badan Perencanaan Pembangunan Daerah (BAPPEDA) of the Konawe District Budget Year 2016. Data are collected through interviews and documentation. Data received from the Badan Perencanaan Pembangunan Daerah (BAPPEDA) Konawe district. The method of analysis used is a method of qualitative desktop function by collecting research data obtained from a research object and other literature. The results of this study show the planning of the appointment and Goals that serve as a guide in BAPPEDA Renstra, where in the Operations Planning many activities which is omitted, if the Rencana Anggaran Satuan Kerja (RASK) does not all can be implemented in accordance with the proposal and the definition of the budget. Availability budget reduction for the whole amount of the budget. Key Word : evaluation of the budget, work unit, regional apparatus, Konawe district.